Droga do uzyskania uprawnień akademickich przez Katolicki Uniwersytet Lubelski w okresie II Rzeczypospolitej - Dębiński, Antoni; Pyter, Magdalena (PRAWO i WIĘŹ, 2025)
This paper explores the lengthy and challenging process through which the Catholic University of Lublin achieved formal equivalence with state academic institutions. This was driven by the fact that only institutions with full academic rights were authorised to carry out comprehensive educational and scholarly activities, including awarding academic degrees and titles. Spanning the period from the university’s establishment in 1918 to its ultimate grant of full academic status in 1938, the paper provides a comprehensive overview of this process. It is primarily grounded in archival materials from the Catholic University of Lublin, relevant literature on the subject, and legal acts governing higher education. The archival resources, which have received limited or fragmented scholarly attention to date, are cited and thoroughly examined in the text using the historical-legal method.